Lipidomic study of the red marine macroalgae as source of bioactive compounds - Azevedo, Vítor Manuel Madureira (2018)
Marine macroalgae, or seaweeds, have gained an increased interest in recent times for the use in various biotechnological applications, due to the added-value of their chemical constituents. Among them, glycolipids and phospholipids display several commercial applications in a wide spectrum of industries, such as food, pharmaceutical and cosmetic. In an effort to further understand the lipid composition of macroalgae, the present work reports, for the first time, the isolation and characterization of the polar lipid profile of the red macroalgae Porphyra dioica cultivated on a land-based integrated multi-trophic aquaculture (IMTA) system, using a lipidomic-based approach employing hydrophilic interaction liquid chromatography-eletrospray ionization mass spectrometry (HILIC-ESI-MS). The fatty acid profile of this species of seaweed was also determined, accounting for season variability and its life cycle. The polar lipid profile of P. dioica revealed the presence of over 69 molecular species, corresponding to glycolipids (sulfoquinovolsyldiacylglycerols, sulfoquinovosylmonoacylglycerols, digalactosyldiacylglycerols) and glycerophospholipids (lyso- and phosphatidylglycerols), lyso- and phosphatidylcholines), as well as phytyl derivatives. Some of these polar lipids contain polyunsaturated fatty acids (PUFAs), namely arachidonic acid (C20:4) and eicosapentaenoic acid (C20:5), thus revealing the ability of P. dioica to biosynthesize this long chain PUFAs. P.dioica from the winter season revealed to be richer in PUFA content, accounting for 37.0% of total fatty acid (TFA) content, as opposed to P. dioica from the summer season (25.0% of TFA content). Eicosapentaenoic acid (EPA) content was revealed to be being significantly higher in the winter season (25.2% of TFA content). The diploid sporophyte conchocelis phase of P. dioica showed to possess the highest amount of PUFAs (47.0% of TFA content), with arachidonic acid being the most abundant fatty acid (21.2% of TFA content). Several of the lipids identified have been reported to possess nutritional and health benefits, thus allowing the valorisation of P. dioica from IMTA as a source of bioactive compounds, adequate for the use in a wide range of different applications and as a functional food, rich in omega-3 fatty acids.